x 3 − 2 4 x 2 + 1 8 0 x − 4 2 0 = 0
A △ A B C has side lengths a , b and c , which are also the roots of the equation above. Find a ( cos C + cos B ) + b ( cos C + cos A ) + c ( cos A + cos B ) . Give your answer to two decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did a long way! Nice solution. +1)
If you didn't know the projection formula (like me):
From Vieta's formula , we have:
a + b + c = 2 4 a b + a c + b c = 1 8 0 a b c = 4 2 0
From cosine rule , we also know that
a 2 = b 2 + c 2 − 2 b c cos A ⟹ cos A = 2 b c b 2 + c 2 − a 2
Similarly, we can find that
cos B = 2 a c a 2 + c 2 − b 2 cos C = 2 a b a 2 + b 2 − c 2
Therefore,
a ( cos B + cos C ) + b ( cos C + cos A ) + c ( cos A + cos B ) = a ( 2 a c a 2 + c 2 − b 2 + 2 a b a 2 + b 2 − c 2 ) + b ( 2 a b a 2 + b 2 − c 2 + 2 b c b 2 + c 2 − a 2 ) + c ( 2 b c b 2 + c 2 − a 2 + 2 a c a 2 + c 2 − b 2 ) = 2 c a 2 + c 2 − b 2 + 2 b a 2 + b 2 − c 2 + 2 a a 2 + b 2 − c 2 + 2 c b 2 + c 2 − a 2 + 2 b b 2 + c 2 − a 2 + 2 a a 2 + c 2 − b 2 = 2 c 2 c 2 + 2 b 2 b 2 + 2 a 2 a 2 = a + b + c = 2 4
That's why I provided a proof for that and its always good to learn new things..Anyways nice colorful solution as usual.... (+1)
Log in to reply
Lol, I don't even know what a circumradius is. I'll learn about it when I find the time
Nice colourful solution!(+1)...Its very easy for those who already knew that projection formula will be used.
Completeness fulfilled! Upvoted!
This is called the projection rule. Its proof is very simple
Call the triangle to ABC And opposite sides be a,b,c .
drop a perpendicular from A Onto BC Call foot of perpendicular to be D.
Now BD+DC = BC (BC = ccos(B) And DC = bcos(C)
Hence bcosc+ccos(B) = a
So the expression asked is nothing but a+b+c which can be found out using vieta's
That's what I did... :-p (1+)
Problem Loading...
Note Loading...
Set Loading...
Group terms and write them as: ( a cos B + b cos A ) + ( a cos C + c cos A ) + ( b cos C + c cos B )
= c + b + a
By Vieta's formula this is
= 2 4
Proof:- a cos B + b cos A = c
Recall circumradius R . Write a = 2 R sin A , b = 2 R sin B and then use sin A cos B + cos A sin B = sin ( A + B ) = sin C so that we are left with 2 R sin C which is nothing but c . In a similar way we can prove other two also so that :
( a cos B + b cos A ) = c ( a cos C + c cos A ) = b ( b cos C + c cos B ) = a
Much popularly known as Projection formula .